2020
DOI: 10.1155/2020/3672517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Boron Nitride Coatings at High Temperatures and Electromagnetic Wave Absorption Properties of Carbon Fiber-Based Magnetic Materials

Abstract: An electromagnetic (EM) wave-absorbing material with a three-layer structure is prepared by depositing magnetic particles and a high-temperature resistant coating on the surface of the carbon fiber (CF) with in situ hybridization. Accordingly, the structure, chemical composition, morphology, high-temperature resistance, EM characteristics, and EM wave absorption of the composite materials were analyzed. The composite materials contained CFs, and the magnetic particles, such as Fe3O4, NiFe2O4, CoFe2O4, and Ni3F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The dashed lines enclose the areas with effective absorption (RL < −10 dB, 90% absorption). The corresponding frequency range is defined as an effective absorption bandwidth (EAB) as many did before. It is apparent that among the four samples, Co/SiC-2 (Figure c) exhibits the optimal microwave absorption performance. At a thickness of 2.8 mm, the EAB is as wide as 8 GHz (ranging from 10 to 18 GHz).…”
Section: Resultsmentioning
confidence: 80%
“…The dashed lines enclose the areas with effective absorption (RL < −10 dB, 90% absorption). The corresponding frequency range is defined as an effective absorption bandwidth (EAB) as many did before. It is apparent that among the four samples, Co/SiC-2 (Figure c) exhibits the optimal microwave absorption performance. At a thickness of 2.8 mm, the EAB is as wide as 8 GHz (ranging from 10 to 18 GHz).…”
Section: Resultsmentioning
confidence: 80%
“…Sun et al reported that composites were fabricated by depositing FeCoNi and BN on the surface of the CF. 87 Compared with common metal oxides, alloys have good thermal stability and magnetic loss. The decomposition temperature of the FeCoNi-BN@CF composite was 1000 1C and its EAB was À15.4 GHz.…”
Section: Carbon Nanotubesmentioning
confidence: 99%